Green Human Resource Management Dan Sustainable Employee Performance Pada Perguruan Tinggi Di Kota Makassar: Peran Mediasi Employee Green Behavior Dan Moderasi Green Organizational Culture - Dhimas Tribuana; Endang Halimah; Andi Masniah; Jahara Jahara; Isiswanty Isiswanty; Koas Dianah (Jurnal Teknologi dan Bisnis Cerdas, 2026)
This study examines how Green Human Resource Management (GHRM) contributes to Sustainable Employee Performance (SEP) in higher education by positioning Employee Green Behavior (EGB) as a mediating mechanism and Green Organizational Culture (GOC) as a moderating condition. A quantitative cross-sectional survey was conducted among 200 lecturers and educational staff working at higher education institutions in Makassar City, Indonesia, from 1 to 14 April 2026. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4 and 5,000 bootstrap subsamples. The measurement model demonstrated satisfactory reliability and validity. The structural results show that GHRM positively affects EGB (beta = 0.487; p < 0.001) and SEP (beta = 0.193; p = 0.001), while EGB positively affects SEP (beta = 0.408; p < 0.001). GOC positively affects EGB (beta = 0.235; p < 0.001) and SEP (beta = 0.274; p < 0.001). EGB significantly mediates the GHRM-SEP relationship (beta = 0.199; p < 0.001), and GOC significantly strengthens the GHRM-EGB relationship (beta = 0.354; p < 0.001). The model explains 41.4% of EGB and 47.2% of SEP variance. The findings extend GHRM research by integrating behavioral mediation and cultural moderation with employee-level sustainable performance, and offer practical directions for embedding sustainability into higher education HR systems and organizational culture.